The impact of osimertinib' line on clonal evolution in EGFRm NSCLC through NGS-based liquid biopsy and overcoming strategies for resistance. (March 2021) - Fuchs, Vered; Roisman, Laila; Kian, Waleed; Daniel, Levin; Dudnik, Julia; Nechushtan, Hovav; Goldstein, Iris; Dvir, Addie; Soussan-Gutman, Lior; Grinberg, Roxana; Gillis, Roni; Peled, Nir
Highlights: Analysis of 30 NGS liquid biopsy tests from EGFRm NSCLC patients at resistance to osimertinib as 1 st or 2 nd line therapy. Mechanisms of resistance differed in 1 st or 2 nd line osimertinib therapy. MET amplification was more common in 1 st line setting; while C797S occurred only in the 2 nd line group. Liquid biopsy was used to guide treatment decision. Combined therapy was well tolerated, and re-exposure to EGFR TKI is feasible. Abstract: Background: Resistance mechanisms following 1st line therapy with osimertinib in EGFR + NSCLC have become focus of investigation. This retrospective study aims to deepen the understanding and clarify possible mechanisms of osimertinib 1st line resistance in comparison to the 2nd line by examining NGS results of 30 patients who developed resistance to osimertinib. Furthermore, we followed clinical outcomes of select patients who received combined therapy following EGFR resistance, a novel strategy not yet widely tested. Methods: Liquid biopsy technique (Guardant360) was used to monitor tumor dynamics in patients who were treated with osimertinib as 1st-line therapy (Group A, N = 15) and patients who received osimertinib as 2nd-line therapy (Group B, N = 15). Results: At the time of progression under osimertinib all but one patient preserved the primary EGFR mutation. While the C797S mutation was relatively common in the 2nd-line osimertinib setting (5/15), it did not develop in group A patients. TP53 was the most common detected mutation among all patients accounting for 11/15 in group A (73.33 %) and 10/15 in group B (66.67 %). In group A MET amplification was found in 3/15 patients (20 %) whereas MET mutation appeared in only one patient from group B. The outcomes of different treatment approaches post osimertinib resistance is reported including chemotherapy with/without osimertinib for maintaining control of brain metastases, drug combination such as osimertinib with crizotinib, chemo-immunotherapy and others. Overall survival in this cohort ranged from 12 to80 months. Conclusions: Mechanisms of resistance to osimertinib as 1st-line therapy differ from those which develop in the 2nd-line setting and commonly include MET amplification. C797S is not a main resistance mechanism in the 1st-line setting, whereas it is more common in the 2nd-line setting. Combined therapy was effective and well tolerated, making it an acceptable choice in patients for whom there is a reasonable rationale for such treatment, however this approach deserves further investigation.